Can Heterosexist Music Cause Hiring Discrimination Against Sexual Minority Men? Testing the Effects of Prejudicial Media Messages. Issue 6 (23rd July 2016) - Binder, Kevin; Ward, L. Monique
Abstract : Workplace heterosexism is a pervasive issue affecting lesbian, gay, bisexual, and transgender (LGBT) employees. This study investigated the influence of heterosexist media on hiring decisions by exposing 171 heterosexual undergraduate men to heterosexist rap music, nonheterosexist rap music, or no music and measuring their evaluations of a heterosexual and gay male professorial job applicant immediately afterward. As expected, participants exposed to the heterosexist music provided lower evaluations of the gay applicant than those exposed to no music, for two of the eight dimensions measured. Also, participants exposed to heterosexist messages were less willing to recommend and meet one-on-one with a gay candidate than a heterosexual one. Music condition effects remained, even with demographic factors controlled. These findings suggest that media heterosexism may affect hiring decisions for GBT men and may also influence the treatment of these men in a workplace environment.